CRISPR-Cas9 Mediated AGO2 Knockout inhibits tumorigenesis in human colorectal cancer cells: CRISPR inhibits tumorigenesis in colorectal cancer cells - Zhu, Yizhi; Wang, Gengfang; Xu, Haoran; Guo, Yuan (Cellular and Molecular Biology, 2024)
AGO2 plays a vital role in small RNA-guided gene silencing, which has been implied in the tumorigenesis of different types of tumors. Fundamentally, increased expression of AGO2 protein is associated with cancer progression and metastasis. This study aims to investigate the molecular mechanism by which AGO2 promotes tumorigenesis in colorectal cancer (CRC). Databases were used to analyze the expression levels of AGO2 in CRC and confirmed by a quantitative reverse transcriptase-PCR (qRT-PCR) assay in CRC tissues and normal adjacent tissues collected from 25 CRC patients. CRISPR/Cas9-mediated genome editing was used to knockout the AGO2 in HCT116 cells as a model system for colorectal cancers. The cell proliferation, migration and invasion ability of HCT116 cells were detected by CCK-8 assay, Wound scratch assay and Transwell assay. Moreover, the quantities of miRNA binding with AGO2 were detected by RNA-Binding Protein Immunoprecipitation (RIP-Assay). We demonstrated that AGO2 was aberrantly high-expressed in 25 matched-tissue pairs of colorectal cancer and para-carcinoma tissue. The following functional experiments verified that knockout of AGO2 suppressed cell proliferation, migration and tumorigenesis to hamper the aggressiveness of CRC. Our study also suggests a possible link between AGO2 and miRNA in RISC. AGO2 was elevated in CRC and knockout of AGO2 suppressed proliferation and tumorigenicity of CRC cells. Moreover, RISC formation and the function of miRNAs are also subject to AGO2. AGO2 may be a meaningful target for CRC therapy.